Delayed cord clamping in term large-for-gestational age infants: A prospective randomised study - YOLDEMİR, AHMET TEVFİK; TEKER SAYIN, AYŞE GÜLSEN; ÖZEK, EREN; BİLGEN, HÜLYA SELVA; ÖZDEMİR, HÜLYA (WILEY, 2019)
Aim To compare the post-natal effects of delayed cord clamping (DCC) and early cord clamping (ECC) in term large-for-gestational age (LGA) infants. Methods This prospective randomised study included 51 term LGA infants. The umbilical cords of these infants were clamped at 15 s in group 1 (ECC group (n = 26)) and at 60 s in group 2 (DCC group (n = 25)). Data for Apgar scores, cord blood, pH and lactate values, second haematocrit, 24th bilirubin levels, duration of hospital stay and admission to the neonatal intensive care unit (NICU) were recorded. Results The demographic characteristics of the infants in the study group were not significantly different. No statistically significant difference was observed in the post-natal haematocrit and bilirubin levels between the groups. Six infants (group 1, n = 3; group 2, n = 3) were diagnosed with polycythaemia (P = 0.79); however, these infants remained asymptomatic, and no treatment was required. One infant in each group developed hyperbilirubinemia, which required phototherapy (P = 1.00). The infant with hyperbilirubinemia in the DCC group presented with asymptomatic polycythaemia. Three neonates in the DCC group required admission to the NICU for transient tachypnoea. Conclusions No significant increase in the rate of post-natal complications of DCC in term LGA infants was observed in the study. However, before recommending DCC on a routine basis, studies with a larger sample size and long-term follow-up are required to elucidate the risks and benefits of DCC in this group of infants.
Keywords: delayed cord clamping; large-for-gestational age infants; newborn; UMBILICAL-CORD; IRON-DEFICIENCY; MANAGEMENT